Climatotherapy in treatment and rehabilitation of children with bronchial asthma complicated with increased meteosensitivity - A. I. Uyanaeva; M. A. Khan; Yu. Yu. Tupitsyna; I. M. Chukina; N. A. Lyan; G. A. Maksimova (Аллергология и Иммунология в Педиатрии, 2023)
Introduction. A topical problem in pediatrics is bronchial asthma, which is characterized by a high prevalence, contributing to the formation of disability and a decrease in the quality of life in children. Possible triggers for exacerbation of the disease include external biotropic weather conditions. In this connection, it is necessary to study and develop new technologies for the correction and prevention of increased meteosensitivity in children with bronchial asthma.Purpose. To study the regularities of the influence of biotropic weather conditions on the course of asthma in children with increased meteosensitivity and to assess the effectiveness of the meteorological influence of climatotherapy.Materials and methods. An assessment was made of the bioclimatic potential of the territory of the Vulan sanatorium, taking into account the thermal regime, the biological effect of solar radiation, the degree of favorable weather conditions for carrying out climatotherapy. The degree of sensitivity to biotropic weather conditions and the features of manifestation of meteopathic reactions were studied in 119 children with asthma at the age of 5 to 15 years. The studies were carried out in a comparative aspect in two groups of children: children in the main group (95 children) in complex spa treatment received dosed climatotherapy procedures; children of the comparison group did not receive climatotherapy.Results. The meteorological dependence of varying severity was found in all children. Weather-related exacerbations in most children developed during the formation of the hypoxic effect of the atmosphere caused by hyperthermia and high humidity, conditions of "stuffiness" and "overheating", increased symptoms of the disease, decreased physical activity, deterioration of the psychoemotional state of children, confirmed by a significant (p <0.05) decrease in values SAN test on average for the group. It was revealed that adequate metered climatic procedures have a positive effect on the clinical course of the disease, contribute to a decrease in severe meteopathic reactions and an increase in the percentage of their mild manifestations.Conclusion. Complex spa treatment with the inclusion of strictly metered climatic procedures (sun and air baths) is one of the possible approaches to the prevention and correction of weather-related exacerbations.